Controls for In-Kind and Monetary Subsidies and Their Rationalization in Islamic Economics and the Possibility of Benefiting from Them in the Egyptian Context - Mohamed, Alaa Basuony Abdel-Raouf; Ag, Anton Akbar, M.; Mohamed, Ahmed Farouk Abbas; Ajeela, Alaa Mustafa Abdel-Maqsoud Abu; El-Naggar, Tamer Fekry Atifa; Sopeah, Wael Aly Ahmed (Journal of Posthumanism, 2025)
This research addresses the controls for in-kind and monetary subsidies in Islamic economics and the impact of adhering to these controls on subsidy allocations, using the Egyptian context as a model. The study reviews the objectives of subsidies in Islamic economics and the regulations concerning eligibility criteria and the amount of entitlement. It also examines the effect of adherence to the Islamic principles of consumer behavior on the number of beneficiaries and the allocation of subsidies in the Egyptian case, while looking ahead at the future in light of implementing Islamic controls for rationalizing in-kind and monetary subsidies. The research concluded that that Islamic controls for providing in-kind and monetary subsidies help rationalize spending and ensure that subsidies reach those who deserve them holds true. Additionally, adherence to Islamic controls for subsidy provision can play a positive role in rationalizing subsidies and their expenditures in the Egyptian context.